PTH-009 Endoscopists Who are Meticulous in their Caecal Image Documentation Detect more Polyps. (4th June 2013) - Thoufeeq, M H; Rembacken, B
Abstract : Introduction: Adenoma detection is now accepted as an important quality indicator of colonoscopy. There is a significant variation in polyp detection rates among colonoscopists. Although the ESGE has recommendations regarding quality of images taken during endoscopy, there are no studies looking at the quality of caecal images versus outcomes of the procedures. Here we tested our hypothesis of endoscopists who have better quality image documentation of the caecum have higher polyp detection. Methods: This retropective study was between June 2011 and May 2012. Planned colonoscopies performed by 16 experienced colonoscopists were included. We excluded procedures with planned therapeutic procedures, inadequate bowel preparation, rectal hyperplastic polyps, bowel cancer screen colonoscopies, previous hemicolectomy and incomplete procedures. The pre-procedure data collected were age and gender of patients, indication of procedures. The intra-procedure data collected were duration of the procedure, number of images stored in the endoscopy database, quality of caecal image, number of polyps (excluding rectal hyperplastic polyps). We cross-checked our pathology database to confirm histology of the polyps. We formulated a new scoring system, caecal image documentation score (CIDS). The CIDS was as follows; no image = 0, unclear image = 1, clear image = 2 and clear image with a label = 3. Results: A total of 651 procedures performed by 16 colonoscopists were analysed. The mean number of procedures performed by each colonoscopist was 41. Mean age of the patients was 60.3 years. 46% of the patients were males. The mean CIDS for the 16 endoscopists was 2.13. The mean polyp detection rate (PDR) was 24% and mean polyp per procedure (PPP) was 0.42. Colonoscopists with mean CIDS > 2.0 (n = 429 procedures, 10 colonoscopists) had PDR of 28% and PPP of 0.52. On the other hand, 6 colonoscopists (222 procedures) with mean CIDS of < 2.0 had PDR of 16% and PPP of 0.24. Mean CIDS > 2.0 was associated with greater PDR (OR 2.1, CI 1.4 – 3.2 p = 0.001). When adjusting for age, gender, and indication for colonoscopy, the mean CIDS > 2.0 remained an independent predictor of greater PDR, OR 2.4, 95% CI 1.5 – 3.8 p < 0.001. Mean CIDS > 2.0 was associated with greater right-sided polyp detection rate, OR 3.4, CI 1.9 – 6.6 p < 0.001. When adjusting for age, gender, and indication for colonoscopy, the mean CIDS > 2.0 remained an independent predictor of greater right-sided PDR, OR 4.0, 95% CI 2.2 – 8.1 p < 0.001. Conclusion: Colonoscopists who are more meticulous in caecal image documentation detect more polyps per procedure and have higher polyp detection rates. Better caecal image documentation also improves right colonic polyp detection. Disclosure of Interest: None Declared.